2020
DOI: 10.1111/ctr.14178
|View full text |Cite
|
Sign up to set email alerts
|

Donor management using a specialized donor care facility is associated with higher organ utilization from drug overdose donors

Abstract: Drug overdoses have tripled in the United States over the last two decades. With the increasing demand for donor organs, one potential consequence of the opioid epidemic may be an increase in suitable donor organs. Unfortunately, organs from donors dying of drug overdose have poorer utilization rates than other groups of brain‐dead donors, largely due to physician and recipient concerns about viral disease transmission. During the study period of 2011 to 2016, drug overdose donors (DODs) account for an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(52 reference statements)
1
5
0
Order By: Relevance
“… 5 A separate study using data from 661 donors managed in the same facility found higher numbers of organs donated from donors that died after drug overdose than national averages, but no differences among donors with other causes of death. 8 This work confirms and extends these prior studies by using a national donor sample, examining outcomes in multiple facilities, and adjusting outcomes for individual donor characteristics and managing OPOs. Adjustment for individual OPO is particularly important given known regional differences in donor characteristics and acute healthcare resources, as well as variation in donor identification, management, and performance among US OPOs.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“… 5 A separate study using data from 661 donors managed in the same facility found higher numbers of organs donated from donors that died after drug overdose than national averages, but no differences among donors with other causes of death. 8 This work confirms and extends these prior studies by using a national donor sample, examining outcomes in multiple facilities, and adjusting outcomes for individual donor characteristics and managing OPOs. Adjustment for individual OPO is particularly important given known regional differences in donor characteristics and acute healthcare resources, as well as variation in donor identification, management, and performance among US OPOs.…”
Section: Discussionsupporting
confidence: 78%
“…Single-facility evaluations have suggested improved organ donation outcomes and several practical advantages over hospital-based recovery, 4 8 but results may not be generalizable to donors in other regions, managing OPOs, or facilities. Furthermore, understanding nationwide effectiveness of OPO-based recovery facilities is complicated by variation in the rates of facility use among OPOs (not all donors in a donor service area are transferred to an OPO-based facility) and known regional differences in donor characteristics and OPO performance.…”
Section: Introduction/backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…After stagnating in the late 2000s, the annual number of deceased donors in the USA began a remarkable and sustained climb, increasing 83% between 2012 (8143 donors) and 2022 (14 903) [2], a rise at least partially associated with the drug overdose epidemic [3]. And as OPO performance has been increasingly scrutinized [4][5][6][7], the donor pool has not only increased but has further broadened with respect to general acceptability criteria for candidacy: in 2022, over 31% of donors were aged 50-64 years, compared with 27% consistently each year from 2012 to 2018 [2].…”
Section: Introductionmentioning
confidence: 99%
“…4 Rapid facility opening 4,5 and model endorsement by a recent National Academies of Science, Engineering, and Medicine report 6 were based on early studies describing operational advantages and improved short-term donation outcomes (as measured by the number of organs transplanted per donor) from a single established OPO-based recovery facility. [7][8][9] However, those studies could not ascertain whether local benefits of OPO-facility use could be extrapolated to other regions and OPOs. To address the question of generalizability, a recent retrospective cohort study of 5010 adult deceased organ donors after brain death managed in 10 U.S. OPO regions demonstrated that donors transferred to OPO-based organ recovery facilities donated more transplanted organs on average than donors who remained in local acute-care hospitals.…”
Section: Introduction/backgroundmentioning
confidence: 99%